PELAKSANAAN PERJANJIAN KERJASAMA PERDAGANGAN BEBAS ASEAN - CINA (ACFTA) TAHUN 2010 DAN IMPLIKASINYA BAGI INDONESIA - Magdariza Magdariza; Delfiyanti Delfiyanti (Faculty of Law, Universitas Diponegoro, 2011)
Nowadays, the development of free trade around A SEAN especially between ASEAN's nations and China through the